Analysis of the Influence of Economic Growth, Unemployment Rates, Poverty Levels on the Level of Community Welfare in the Regency/City of Bali Province - Sherin Eknandya Juliantika; Sudarsana Arka (International Journal of Economics and Management Sciences, 2024)
A good country's economy can be seen from the level of prosperity of its people. To see the welfare of society in a country, it can be measured by the Human Development Index (HDI). The level of social welfare between regions indicates that there is inequality between regions. The objects of this research are 9 regencies/cities in Bali Province. The descriptive quantitative method used in this research is the Secondary Data Analysis (ADS) approach. Based on the results of the analysis, it can be concluded that partial economic growth has a positive and significant effect on the welfare of the people in districts/cities in Bali Province. The unemployment rate partially has a positive and significant effect on the welfare of the people in the Regencies/Cities in Bali Province and the poverty rate partially has a positive and insignificant effect on the welfare of the people in the Regencies/Cities in the Province of Bali.